Pemberdayaan UMKM Waliyyu Snack melalui Penguatan Digital Marketing dan Sistem Pencatatan Keuangan Sederhana: Pengabdian - Yolanda, Faras; Andini, Rustiana; salsabila, getsha; Wahyudi, Robby (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The Community Service Course (KPB) or Field Work Practice (PKL) was conducted at Waliyyu Snack, located in Sukamanah Village, Bojong District, Purwakarta Regency. This KPB-PKL program aimed to optimize the management of Waliyyu Snack’s business through the implementation of digital marketing strategies and simple financial recording. The main issues identified included underutilization of digital marketing media, simple packaging design, and manual transaction recording without a standardized format. The methods employed comprised field observation, consultation, training and mentoring, and applied science and technology simulations to practice the use of digital media and recording formats directly, making them easy for the business owner to implement. The program outcomes included support in digital marketing, such as creating Shopee and Instagram accounts, registering the UMKM on Google Maps, generating product barcodes, designing packaging, and training in simple financial recording. These activities had a positive impact on the UMKM, enabling them to improve business management quality and expand their marketing reach.